RNA Interference Suppression of v-ATPase B and Juvenile Hormone Binding Protein Genes Through Topically Applied dsRNA on Tomato Leaves: Developing Biopesticides to Control the South American Pinworm, Tuta absoluta (Lepidoptera: Gelechiidae) - Ramkumar, Govindaraju; Asokan, Ramasamy; Prasannakumar, N. R.; Kariyanna, B.; Karthi, Sengodan; Alwahibi, Mona S.; Elshikh, Mohamed Soliman; Abdel-Megeed, Ahmed; Ghaith, Aml; Senthil-Nathan, Sengottayan; Kalaivani, Kandaswamy; Hunter, Wayne Brian; et al. (Frontiers in Physiology, 2021)
South American pinworm, Tuta absoluta (Meyrick) (Family: Gelechiidae) is one of the most devastating lepidopteran pests in developing countries of South America, Africa and Asia. This pest is classified as the most serious threat for tomato production worldwide. In the present study we analyzed RNAi-mediated control, through exogenously applied dsRNA delivery on tomato. The dsRNA treatments were made to target the Juvenile Hormone Binding Protein and the v-ATPase B Both mRNA targets were cloned, validated by sequencing, and used to produce each dsRNA. After treatments the relative transcript expression was analysed using qRTPCR to assess to efficacy of RNAi. A leaf-dip assay was used to provide late 2ndinstar larvae three feeding access periods: 24, 48, and 72 hr, to evaluate the effect of gene silencing of each target. Larvae were fed tomato leaves coated with five different RNAi concentrations (10, 20, 30, 40 and 50 micrograms/ centimetre-squared), that suppressed two genes (Juvenile Hormone Protein, JHBP, and Vacuolar-type adenosine triphosphatase enzyme, v-ATPase). Treatments with dsRNA’s showed significant increase in mortality at 24, 48 and 72 hours after ingestion, (P <0.01, α=0.05), along with reduced leaf damage, and increased feeding deterrence. The results suggest these two RNAi products may provide a suitable treatment to be developed for control of this and other lepidopteran pests.